De Novo Design of Covalent Organic Framework Membranes toward Ultrafast Anion Transport. Issue 36 (26th July 2020) - He, Xueyi; Yang, Yi; Wu, Hong; He, Guangwei; Xu, Zhongxing; Kong, Yan; Cao, Li; Shi, Benbing; Zhang, Zhenjie; Tongsh, Chasen; Jiao, Kui; Zhu, Kongying; et al.
Abstract: The emergence of all‐organic frameworks is of fundamental significance, and designing such structures for anion conduction holds great promise in energy conversion and storage applications. Herein, inspired by the efficient anion transport within organisms, a de novo design of covalent organic frameworks (COFs) toward ultrafast anion transport is demonstrated. A phase‐transfer polymerization process is developed to acquire dense and ordered alignment of quaternary ammonium‐functionalized side chains along the channels within the frameworks. The resultant self‐standing COFs membranes exhibit one of the highest hydroxide conductivities (212 mS cm −1 at 80 °C) among the reported anion exchange membranes. Meanwhile, it is found that shorter, more hydrophilic side chains are favorable for anion conduction. The present work highlights the prospects of all‐organic framework materials as the platform building blocks in designing ion exchange membranes and ion sieving membranes. Abstract : The de novo design of covalent organic frameworks (COFs) affords a dense and ordered alignment of quaternary ammonium‐functionalized side chains along the intrinsic channels within the frameworks, rendering one of the highest hydroxide conductivities among the reported anion‐exchange membranes (AEMs), and demonstrating the feasibility of COFs as the building blocks for high‐performance AEMs.